Evaluation and identification of resistance lines and QTLs of maize to seedborne Fusarium verticillioides - Ma, Peipei; Haojie Li; Liu, Enpeng; He, Kewei; Song, Yunxia; Dong, Chaopei; Wang, Zhao; Zhang, Xuecai; Zhou, Zijian; Xu, Yufang; Wu, Jianyu; Zhang, Huiyong (Scientific Societies, 2022)
Internal fungal contamination in cereal grains may affect plant growth and result in health concerns for humans and animals. Fusarium verticillioides is a seedborne fungus that can systemically infect maize. However, few efforts had been devoted to studying the genetics of maize resistance to seedborne F. verticillioides. In this study, we developed a disease evaluation method to identify resistance to seedborne F. verticillioides in maize, by which a set of 121 diverse maize inbred lines were evaluated. A 160 F10-generation recombinant inbred line (RIL) population derived from a cross of the resistant (BT-1) and susceptible (N6) inbred line was further used to identify major quantitative trait loci (QTLs) for seedborne F. verticillioides resistance. Eighteen inbred lines with a high resistance to seedborne F. verticillioides were characterized and could be used as potential germplasm resources for genetic improvement of maize resistance. Six QTLs with high heritability across multiple environments were detected on chromosomes 3, 4, 6, and 10, among which was a major QTL, qISFR4-1. Located on chromosome 4 at the interval of 12922609-13418025, qISFR4-1 could explain 16.63% of the total phenotypic variance. Distinct expression profiles of eight candidate genes in qISFR4-1 between BT-1 and N6 inbred lines suggested their pivotal regulatory roles in seedborne F. verticillioides resistance. Taken together, these results will improve our understanding of the resistant mechanisms of seedborne F. verticillioides and would provide valuable germplasm resources for disease resistance breeding in maize.